PERCEPTIONS AND EXPERIENCES OF PRE-SERVICE AND IN-SERVICE TEACHERS REGARDING INCLUSIVE EDUCATION IN KAZAKHSTAN - Ungutbayeva, Aisha (Nazarbayev University Graduate School of Education, 2025)
This phenomenological study aimed at identifying the perceptions and experiences of pre-service and in-service teachers regarding inclusive education in Kazakhstan. Although Kazakhstan strives to make schools inclusive by adding courses on inclusive education at pedagogical universities, the implementation of inclusive education remains a challenge. This study aimed to address this gap, and it was guided by the following research questions: (1) How do pre-service and in-service teachers perceive inclusive education? (2) How do pre-service and in-service teachers experience inclusive education? (3) How do they perceive their training on inclusive education? (4) What are the implications of the findings for policy, practice and research? Data was collected using semi-structured face-to-face in-depth interviews with five pre-service and five in-service teachers, all of whom were students or graduates of the same pedagogical university. Pre-service teachers were in their fourth year, while in-service teachers graduated no more than ten years ago. Data was analysed thematically. There were four key findings. 1] Teachers often confuse inclusive education with special education. 2] Pre-service teachers receive insufficient training on inclusive education. 3] In-service teachers struggle with inclusive practices due to lack of practical training. 4] Mainstream schools often depend on unqualified tutors. The thematic analysis revealed that both pre-service and in-service teachers confuse inclusive education with special education, primarily discussing students with disabilities. The findings of this study indicate a significant gap between theory and practice, making university courses unhelpful and lacking in systematization. Additionally, there is a lack of training suggested for in-service teachers in schools. The study highlights the importance of accurately conceptualizing inclusive education in university courses and providing systematic, mandatory hands-on training for in-service teachers. The study utilized Bronfenbrenner’s ecological system and adds to the literature on the perceptions and experiences of both pre-service and in-service teachers regarding inclusive education and offers recommendations for schools, the education system, and training to improve the implementation of inclusive education practices in schools. Keywords: pre-service teachers, in-service teachers, inclusive education, diverse students , mainstream schools, university courses, hands-on training.
Keywords: in-service teachers; inclusive education; diverse students; mainstream schools; university courses; hands-on training.; pre-service teachers; Type of access: Embargo